Evaluation of Interactive Learning Through the Quizizz Application at MTsN 2 Payakumbuh City - Latifa, Maysa; Pratama, Andy Riski; Hasan, Rahmat Hidayat; Kamal, Muhiddinur; Zakir, Supratman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research is motivated by conditions that require educators to look for solutions to evaluate interactive learning by utilizing Android in the Industry 5.0 era. The quizizz application is a game-based and multi-game educational application that makes assessment using quizizz more fun because there are game elements in it. So that the use of this application is effective for use in learning assessment. The purpose of this writing is to identify an evaluation of interactive learning through the quizizz application at MTsN 2 Payakumbuh City. The research method presented is quantitative descriptive research using research techniques using questionnaires. The research subjects involved 30 students of MTsN 2 Payakumbuh City class VII 3. The findings of this research show that the average percentage of approaches in the Strongly Agree (SS) category is 23.86%, Agree (S) is 41.37%, Quite Agree (CS) at a percentage of 22.47%, Disagree (TS) at a percentage of 6.42%, Strongly Disagree (STS) at a percentage of 1.83%. The conclusion of this research shows that the Quizizz application media can improve student learning outcomes. The implications of this research indicate that there needs to be optimization in implementing the Quizzizz application on a larger scale, so that the data obtained is more accurate and the Quizizz application can be considered for use as an interactive learning evaluation tool that can be used via Android.